2015
DOI: 10.1016/j.nefro.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of impact of hemodialysis and renal transplantation on cognitive functions in ESRD patients

Abstract: Renal transplantation as a modality of treatment, in ESRD patients, is superior to hemodialysis in terms of cognitive performance improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 12 publications
3
15
1
4
Order By: Relevance
“…In this investigation, hematocrit was associated with working memory (Letters and numbers), in line with previous findings [42]. Hemoglobin, which has previously been related to neuropsychological performance in ESRD-HD [3, 8], was associated with figural fluency (RFFT total design) in our study. No association was observed between Kt/v value and performance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this investigation, hematocrit was associated with working memory (Letters and numbers), in line with previous findings [42]. Hemoglobin, which has previously been related to neuropsychological performance in ESRD-HD [3, 8], was associated with figural fluency (RFFT total design) in our study. No association was observed between Kt/v value and performance.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding verbal fluency, Harciarek et al [24] found a reduced rate of word production of in phonological fluency tasks, while Post et al [25], also using the COWAT, reported worse performance in phonological and semantic verbal fluency. Regarding working memory, Anwar et al [8] and Costa et al [13] observed lower performance by ESRD-HD patients relative to HCs. Previous studies [3, 25] also found impaired inhibitory control in ESRD-HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, considering partly double prevalence of the two treatments and the side effects followed by each of them, several studies have been conducted on comparing two treatments in all of which the effect of treatments on the life quality has been studied to compare these treatments (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%